Post refractory CPR due to STEMI with three vessels disease complicated cardiac arrest, is it possible to recover the heart after revascularization by PCI post extracorporeal cardio pulmonary resuscitation (ECPR)? - A.A. Rabie; S. Alasmari; A. Asiri; M. Alsherbini; W. Alqassem; M. Rajab; E. Alenazi; J. Thomas (Egyptian Journal of Critical Care Medicine, 2018)
High-risk percutaneous coronary intervention (PCI) remains a viable revascularization strategy for complex coronary arteries diseases. Selective PCI supported by extracorporeal membrane oxygenation (ECMO) is also a viable alternative for patients those are at very high risk for coronary artery bypass grafting (CABG). Extracorporeal membrane oxygenation (ECMO) can direct blood flow from the body to membrane oxygenator then return it back to the body. Thus completely/partially replacing the function of the heart and lungs to increasing the likelihood of functional recovery. We will present a case of refractory CPR post STMI rescued by ECPR with revascularization of three coronary vessels after percutaneous coronary intervention (PCI) under mechanical support of extracorporeal membrane oxygenation (ECMO) after exclusion of surgical choice due to patient risk condition. We think that in selected group of highly critical cases PCI with MCS could replace the need of major surgical intervention like CABG. Keywords: High risk PCI, ECMO, ECPR, Multi vessels diseases